Effect of KIT and PDGFRA mutations on survival in patients with gastrointestinal stromal tumors treated with adjuvant imatinib: an exploratory analysis of a randomized clinical triala - Joensuu, Heikki; Hohenberger, Peter (JAMA oncology, 2017)
Importance Little is known about whether the duration of adjuvant imatinib influences the prognostic significance of KIT proto-oncogene receptor tyrosine kinase (KIT) and platelet-derived growth factor receptor α (PDGFRA) mutations. Objective To investigate the effect ofKITandPDGFRAmutations on recurrence-free survival (RFS) in patients with gastrointestinal stromal tumors (GISTs) treated with surgery and adjuvant imatinib. Design, Setting, and Participants This exploratory study is based on the Scandinavian Sarcoma Group VIII/Arbeitsgemeinschaft Internistische Onkologie (SSGXVIII/AIO) multicenter clinical trial. Between February 4, 2004, and September 29, 2008, 400 patients who had undergone surgery for GISTs with a high risk of recurrence were randomized to receive adjuvant imatinib for 1 or 3 years. Of the 397 patients who provided consent, 341 (85.9%) had centrally confirmed, localized GISTs with mutation analysis forKITandPDGFRAperformed centrally using conventional sequencing. During a median follow-up of 88 months (completed December 31, 2013), 142 patients had GIST recurrence. Data of the evaluable population were analyzed February 4, 2004, through December 31, 2013. Main Outcomes and Measures The main outcome was RFS. Mutations were grouped by the gene and exon.KITexon 11 mutations were further grouped as deletion or insertion-deletion mutations, substitution mutations, insertion or duplication mutations, and mutations that involved codons 557 and/or 558. Results Of the 341 patients (175 men and 166 women; median age at study entry, 62 years) in the 1-year group and 60 years in the 3-year group), 274 (80.4%) had GISTs with aKITmutation, 43 (12.6%) had GISTs that harbored aPDGFRAmutation, and 24 (7.0%) had GISTs that were wild type for these genes.PDGFRAmutations andKITexon 11 insertion or duplication mutations were associated with favorable RFS, whereasKITexon 9 mutations were associated with unfavorable outcome. Patients withKITexon 11 deletion or insertion-deletion mutation had better RFS when allocated to the 3-year group compared with the 1-year group (5-year RFS, 71.0% vs 41.3%;P < .001), whereas no significant benefit from the 3-year treatment was found in the other mutational subgroups examined.KITexon 11 deletion mutations, deletions that involved codons 557 and/or 558, and deletions that led to pTrp557_Lys558del were associated with poor RFS in the 1-year group but not in the 3-year group. Similarly, in the subset withKITexon 11 deletion mutations, higher-than-the-median mitotic counts were associated with unfavorable RFS in the 1-year group but not in the 3-year group. Conclusions and Relevance Patients withKITexon 11 deletion mutations benefit most from the longer duration of adjuvant imatinib. The duration of adjuvant imatinib modifies the risk of GIST recurrence associated with someKITmutations, including deletions that affect exon 11 codons 557 and/or 558. Trial Registration clinicaltrials.gov Identifier:NCT00116935